Intradermal electrical stimulation of sudomotor nerves and local sweat rate - Mack, Gary W.; Bahr, Kaylee M.; McEwan, Christian J.; Price, Carson J.; Renfro, Ashton J. (American journal of physiology. Regulatory, integrative and comparative physiology, 2025)
Neuron discharge variability can offer some advantages to a downstream physiological response. We examined this possibility with respect to sudomotor nerve activity and local sweat rate. Variable neuron discharge activity, induced by intradermal electrical stimulation, did not have an impact on the peak local sweat rate but did reduce the time to sweating onset and the stimulus intensity required to reach 50% of peak sweating (EC 50 ). The local sweat rate (LSR) response to intradermal electrical stimulation generates a sigmodal stimulus-response curve with a peak sweat rate generated during a 30-s period of continuous stimuli at a frequency of 16–32 Hz. However, the in vivo firing pattern of the sudomotor nerve resembles more of a bursting pattern. We tested the hypothesis that a bursting pattern during intradermal electrical stimulation would result in a greater sweating response than the regular continuous stimulus pattern. Fifteen subjects were studied in a temperature-controlled room at 27.6 ± 0.2°C. The LSR was measured with a miniature sweat capsule with guide sleeves for holding the intradermal stimulating electrodes. The nine continuous stimulus frequencies (0.2, 1, 2, 4, 8, 12, 16, 32, and 64 Hz) were compared to a bursting pattern with a similar total number of stimuli. The sweating response was determined as the area under the ∆LSR-time curve. Peak ∆LSR was slightly higher for the continuous stimuli (0.396 ± 0.242 mg·min −1 ·cm −2 , P = 0.023) than for the bursting stimuli (0.356 ± 0.244 mg·min −1 ·cm −2 ). The sigmoidal-shaped stimulus-response curves, however, were significantly different ( P = 0.0007). The stimulus frequency producing 50% of peak LSR (EC 50 , P = 0.0029) was higher during continuous stimulation and the Hill slope was lower ( P < 0.0001) during bursting stimuli. These data do not support the concept that a bursting stimulus pattern during intradermal electrical stimulation evokes a greater ∆LSR. NEW & NOTEWORTHY Neuron discharge variability can offer some advantages to a downstream physiological response. We examined this possibility with respect to sudomotor nerve activity and local sweat rate. Variable neuron discharge activity, induced by intradermal electrical stimulation, did not have an impact on the peak local sweat rate but did reduce the time to sweating onset and the stimulus intensity required to reach 50% of peak sweating (EC 50 ).